Primary Purpose for Committing a Crime and Past-30 Day Opioid Misuse: A Statewide Sample of Justice-Involved Children - Shaw, Dylan J. (Journal of drug issues, 2022)
The prevalence of opioid misuse (OM) among justice-involved children (JIC) is significantly higher than children in the general population, yet little research has examined the predictors of OM among JIC. Goldstein’s “economic compulsive model” hypothesizes that JIC who commit crimes for material gain will have a higher likelihood of meeting past-30 day (P30D) OM criteria. The data in this study were cross-sectional and represented 79,960 Florida JIC. To test the hypothesis, logistic regression analyses were utilized. Over 2000 JIC (2.67%) met P30D OM criteria and JIC who committed crimes for material gain were 2.55 times as likely to meet P30D OM criteria. Findings indicate that children may be incarcerated due to an inability to afford their addiction, contributing to the criminalization of mental health. JIC could benefit from the increased utilization of drug courts and the implementation of a cascade of care model.